Understanding and managing model risk : a practical guide for quants, traders and validators - Morini, Massimo (Wiley Online Library., 2011)
"A guide to the validation and risk management of quantitative models used for pricing and hedging. Whereas the majority of quantitative finance books focus on mathematics and risk management books focus on regulatory aspects, this book addresses the elements missed by this literature--the risks of the models themselves. This book starts from regulatory issues, but translates them into practical suggestions to reduce the likelihood of model losses, basing model risk and validation on market experience and on a wide range of real-world examples, with a high level of detail and precise operative indications"--